Web-Based Unwaha Cooperative Management Information System - Siti Sufaidah; Zuke Ernanda Putri (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
In carrying out activities in the campus environment, a program is needed to carry out these activities well. One of them is a web application. Web is a general name for the World Wide Web, which is basically an internet server system that supports documents in a special format in the Hyper Text Markup Language language, web use can also be applied in marketing activities. The purpose of this research is to build a cooperative management information system at KH University. A. Wahab Hasbullah web-based. With this application, it is hoped that it can help marketing activities in cooperatives for admins and members. The result of this research is the cooperative web application of KH University. A. Wahab Hasbullah for admins and cashiers in controlling economic activities in cooperatives such as product input, viewing product categories